SPECTROPHOTOMETRIC DETERMINATION OF COBALT(II), NICKEL(II) AND COPPER (II) WITH 1-(2 PYRIDYLAZO)-2-NAPHTHOL IN MICELLAR MEDIUM - Shar, G. A.; Soomro, G. A. (The Nucleus, 2020)
Spectrophotometeric determination of cobalt(II), nickel(II) and copper(II) is carried out with 1-(2 pyridylazo)-2-naphthol as a complexing reagent in aqueous phase using non-ionic surfactant Tween 80. Beerâ€™s law is obeyed for Co(II), Ni(II) and Cu(II) over the range 0.5 - 4.0, 0.5 - 4.0 and 0.5 - 3.0 ngmL-1 with detection limit (2Ïƒ) ï€ of 6.7, 3.2 and 3.9 ngmL-1. The ï¬max molar absorption, molar absorptivity, Sandell’s sensitivity of Co(II), Ni(II) and Cu(II) are 580 nm, 570 nm and 555 nm; ï¥ max ï‚´ (104 mol-1 cm -1) is 0.87, 1.8 and 1.6 and 6.8, 3.3 and 3.9 ng cm-2 respectively. The pH at which complex is formed for Co(II), Ni(II) and Cu(II) is 5, 5.5 and 6.5 respectively. The critical micelle concentration (CMC) of Tween 80 is 5%. The present method is compared with that of atomic absorption spectroscopy and no significant difference is noted between the two methods at 95% confidence level. The method has been applied to the determination of Co(II), Ni(II) and Cu(II) in industrial waste water and pharmaceutical samples